Radiation for diffuse large B‐cell lymphoma in the rituximab era: Analysis of the National Comprehensive Cancer Network lymphoma outcomes project. Issue 7 (9th December 2014) - Dabaja, Bouthaina S.; Vanderplas, Ann M.; Crosby‐Thompson, Allison L.; Abel, Gregory A.; Czuczman, Myron S.; Friedberg, Jonathan W.; Gordon, Leo I.; Kaminski, Mark; Niland, Joyce; Millenson, Michael; Nademanee, Auayporn P.; Zelenetz, Andrew; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND The role of consolidation radiotherapy was examined for patients with diffuse large B‐cell lymphoma who were treated at institutions of the National Comprehensive Cancer Network during the rituximab era. METHODS Failure‐free survival (FFS) and overall survival (OS) were analyzed in terms of patient and treatment characteristics. Potential associations were investigated with univariate and multivariate survival analysis and matched pair analysis. RESULTS There were 841 patients, and most (710 or 84%) received 6 to 8 cycles of rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R‐CHOP); 293 (35%) received consolidation radiation therapy (RT). Failure occurred for 181 patients: 126 patients (70%) who did not receive RT and 55 patients (30%) who did. At 5 years, both OS and FFS rates were better for patients who had received RT versus those who did not (OS, 91% vs 83% [P = .01]; FFS, 83% vs 76% [P = .05]). A matched pair analysis (217 pairs matched by age, stage, International Prognostic Index [IPI] score, B symptoms, disease bulk, and response to chemotherapy) showed that the receipt of RT improved OS (hazard ratio [HR], 0.53 [P = .07]) and FFS (HR, 0.77 [P = .34]) for patients with stage III/IV disease, but too few events took place among those with stage I/II disease for meaningful comparisons (HR for OS, 0.94 [P = .89]; HR for FFS, 1.81 [P = .15]). A multivariate analysis suggested that the IPI score and the response to chemotherapy had the greatest influence on outcomes. CONCLUSIONS There was a trend of higher OS and FFS rates for patients who had received consolidation RT after R‐CHOP (especially for patients with stage III/IV disease), but the difference did not reach statistical significance. Cancer 2014. © 2014 American Cancer Society. Cancer 2015;121:1032–1039. © 2014 American Cancer Society.